1985
DOI: 10.1111/j.1365-2141.1985.tb07361.x
|View full text |Cite
|
Sign up to set email alerts
|

The myelodysplastic syndromes: different evolution patterns based on sequential morphological and cytogenetic investigations

Abstract: Serial morphological and cytogenetic investigations were performed in 46 patients with the myelodysplastic syndrome (MDS). Twenty-one patients (45.5%) progressed to AML (greater than 30% blasts in bone marrow smears). Based on sequential determinations of percentages of bone marrow blasts, three patterns of evolution were observed in MDS. Patients with evolution pattern A (48%) had an apparently stable disease with minimal or no increase in bone marrow blasts. Exceptionally they developed new or additional chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
3

Year Published

1986
1986
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(42 citation statements)
references
References 14 publications
3
36
0
3
Order By: Relevance
“…Numerous reports have demonstrated that MDS karyotype abnormalities significantly affect OS and the risk of MDS/AML progression, [6][7][8][9][10][11][12][13][14][15][18][19][20][21][22][23][24][25][26] even in patients undergoing intensive chemotherapies. 27,28 Therefore, in 1997 the IPSS 15 grouped MDS patients (either untreated or submitted to low-dose chemotherapy or growth factors only) into three prognostically different cytogenetic categories and included the chromosome pattern in a new scoring system which has been validated by various reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous reports have demonstrated that MDS karyotype abnormalities significantly affect OS and the risk of MDS/AML progression, [6][7][8][9][10][11][12][13][14][15][18][19][20][21][22][23][24][25][26] even in patients undergoing intensive chemotherapies. 27,28 Therefore, in 1997 the IPSS 15 grouped MDS patients (either untreated or submitted to low-dose chemotherapy or growth factors only) into three prognostically different cytogenetic categories and included the chromosome pattern in a new scoring system which has been validated by various reports.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][18][19][20][21][22][23][24][25][26] Chromosome defects were more common in RAEB and RAEB-t than in RARS and RA. Deletions or gains of entire chromosomes had an incidence of 60.4% and translocations of only 1.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquired chromosomal abnormalities are found in approximately 33-66% of patients with MDS. 85,86 Analysis of G6PD and cytogenetics strongly suggested that a multipotent progenitor was involved in sideroblastic anemia in two patients. 87,88 In addition to marrow cells, erythrocyte, granulocytes and platelets, 21 of 24 EBV-transformed lymphoid lines from one of these patients displayed the same G6PD type.…”
Section: Myelodysplastic Disordersmentioning
confidence: 99%
“…Transformation to AML is a frequent event in MDS, in which cytogenetic evolution is assumed to play a role [1,3,12]. We describe a patient who presented with MDS (RAEB) and subsequently developed Ph positive CML in the chronic phase then evolved rapidly to the blastic phase.…”
Section: Discussionmentioning
confidence: 98%